PERTANGGUNGJAWABAN PIDANA PELAKU PASIF DALAM TINDAK PIDANA PENCUCIAN UANG - Savira Fatma Adriani Hasibuan (2022)
Money Laundering is the use of assets derived from several predicate crimes. The perpetrators of the crime of money laundering are divided into 2 (two), namely active actors and passive actors, as stated in Article 3 and Article 5 of Law no. 8 of 2010 concerning the Crime of Money Laundering. This study aims to compare the crime and liability of passive perpetrators of money laundering and the legal protection they receive. In achieving this goal, this research uses a normative juridical method, which refers to normative provisions or regulations regarding the crime of money laundering. The result of this study is the finding of a comparison of liability and legal protection given to two decisions from different cases, namely the first is Mens Rea from a case that does not know the origin of the crime and is only promised something by an active perpetrator and there is also passive actors who help disguise the origin of assets resulting from the Crime of Money Laundering based on their status as wives and their obedience to their husbands, who are active perpetrators. In addition, there is protection for passive perpetrators of money laundering based on the principles of carelessness and ignorance to be the defense of the passive perpetrator, so that the punishment imposed is not as severe as the active perpetrator.